Electricity Production from Wind Energy By Piezoelectric Material - Büyükkeskin, İkram; Tekin, Sezai Alper; Gürel, Seyfettin; Genç, Mustafa Serdar (Center of Biomass & Renewable Energy, Diponegoro University, 2019)
In recent years, the energy demand has increased, and alternative way of energy production methods are proposed to deal with this phenomenon by scholars. One of the most promising method is piezoelectric materials. These materials can be used for energy production with improving their efficiencies. This work is made with the guidance of one project which aimed to electricity production form wind energy. This method with one prototype is investigated. Two different wind stalk structures are produced with 3-D Printer. These different structures are set up in wind tunnel and it is experimented under different wind speeds and high turbulence flows. As a result, a circular and four-corner wind stalk structures are investigated for low and high turbulence flows in several wind speeds. To conclude, the produced energy is too small for the systems in market because there are many types of piezoelectric materials for various applications and the problems due to measurement devices. However, piezoelectric materials can be better alternative for classical wind turbines in turbulence flow areas. Therefore, the electricity production from piezoelectric material will be promising method in the future with its advantages.© 2019. CBIORE-IJRED. All rights reservedArticle History: Received May 15th 2018; Received in revised form September 14th 2018; Accepted January 5th 2019; Available onlineHow to Cite This Article: Buyukkseskin, I., Tekin, S. A., Gurel, S., Genc, M S. (2019) Electricity Production from Wind Energy By Piezoelectric Material. International Journal of Renewable Energy Develeopment, 8(1), 41-46.https://doi.org/10.14710/ijred.8.1.41-46